2018
DOI: 10.1016/j.ajog.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Early prognostic factors of outcomes in monochorionic twin pregnancy: systematic review and meta-analysis

Abstract: It is not currently possible to predict adverse outcomes in monochorionic twin pregnancies. We have revealed a lack of research investigating first-trimester biomarkers in monochorionic twin pregnancies. Different assessment methods and definitions of each variable and outcome were an issue and this highlights the need for a large cohort study to evaluate these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 69 publications
0
22
0
2
Order By: Relevance
“…To date, there are no effective screening tests to determine adverse outcomes for monochorionic twins in the first trimester [19]. At the early second trimester of 16 to 18 weeks of gestation, it has been reported that intertwin differences in anthropometric measurements such as abdominal circumference, femur length, head circumference, and fetal weight could not predict progression to TTTS, or composite neonatal outcomes including respiratory distress syndrome, intraventricular hemorrhage, an Apgar score less than 7, necrotizing enterocolitis, early-onset sepsis, and neonatal death [20].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no effective screening tests to determine adverse outcomes for monochorionic twins in the first trimester [19]. At the early second trimester of 16 to 18 weeks of gestation, it has been reported that intertwin differences in anthropometric measurements such as abdominal circumference, femur length, head circumference, and fetal weight could not predict progression to TTTS, or composite neonatal outcomes including respiratory distress syndrome, intraventricular hemorrhage, an Apgar score less than 7, necrotizing enterocolitis, early-onset sepsis, and neonatal death [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although ethnicity was not an exclusion criterion, it was only possible to include one ethnicity in this cohort which is a limitation, but does mean that ethnicity was not a confounding factor [24]. One reason for this may be that Caucasian women have been shown to possibly be at higher risk for TTTS [23]. Continued research in this area, with larger cohorts in different countries using translated questionnaires with appropriate validation is required.…”
Section: Discussionmentioning
confidence: 99%
“…Es wurden einige frühe Ultraschallzeichen (Diskordanz in der Scheitel-Steiß-Länge und Nackentransparenz sowie Ductus-venosus-Pathologie) als Prädiktoren für ein späteres TTTS beschrieben [30,31]. Diese haben den Nachteil des geringen positiven Vorhersagewertes.…”
Section: Schwangerschaftsausgangunclassified